PENERAPAN MODEL PEMBELAJARAN CARD SORT DALAM MENINGKATKAN PRESTASI MATA PELAJARAN IPA DI KELAS V MI HIKMATUN NAJAH DESA DOLOGAN - Zubaidi (Sekolah Tinggi Agama Islam (STAI) Khozinatul Ulum Blora, 2018)
Application of Card Sort Learning Method in Increasing Science Subject Achievement in Class V of MI Hikmatun Najah Desa Dologan, Japah District, Blora District, Central Java. This study aims to find out 1) the Cart Sort Learning Model at MI Hikmatun Najah Desa Dologan. 2) Science learning achievement at MI Hikmatun Najah Desa Dologan. 3) Effect of Card Sort Learning Method on Science learning achievement of Grade V students of MI Hikmatun Najah Desa Dologan. The data of this study used quantitative descriptive analysis Hypothesis testing showed that the card sort learning model had an effect on Science Learning Achievement of Grade V students of MI Hikmatun Najah Dologan Blora Regency. This was proven by: 1. What is the Card Sort learning model at MI Hikmatun Najah Desa Dologan. Distribution of questionnaires to 26 respondents about the application of the Card sort method in student learning analyzed showed a value of 65% in the position of 56% - 75%. 2) What is the learning achievement of science at MI Hikmatun Najah Desa Dologan. From the results of the learning calculation students have analyzed the value of 82% in the position of 76% -100%. It was concluded that science learning achievements in MI V Class Hikmatun Najah Dologan , Blora District Good. 3) Is there any effect on the application of the card sort learning method to the students' learning achievement of science in Class V of MI Hikmatun Najah Desa Dologan, Blora Regency, so that there is a moderate or sufficient correlation. Based on the calculation results of rxy = 0.618 which is then consulted with the interpretation table means that there is a moderate or sufficient correlation